Survivin Measurement improves Clinical Prediction of Transition From Arthralgia to RA—Biomarkers to Improve Clinical Sensitivity of Transition From Arthralgia to RA - Erlandsson, Malin C.; Turkkila, Minna; Pullerits, Rille; Bokarewa, Maria I. (Frontiers in Medicine, 2018)
Background: Arthralgia often predates development of rheumatoid arthritis (RA). A set of clinical joint symptoms assisting recognition of patients during their transition from arthralgia to RA, has been recently proposed. Aim: To combine clinical and serological markers aiming to improve recognition of imminent rheumatoid arthritis (RA) among patients with arthralgia. Methods: The total of 1743 first-visit patients attending the rheumatology ward in Gothenburg for joint symptoms were identified during 12 consecutive months. Among those, 63 patients were classified as RA, 73 had undifferentiated arthritis and 180 had unexplained arthralgia. New cases of RA, which developed during the prospective follow-up of 48 months, comprised the preclinical (pre-)RA group. The set of joint symptoms was applied to the first-visit records aiming to distinguish a) patients with arthralgia and arthritis, b) patients with pre-RA, who later develop the disease, and the receiver operating characteristics curves were constructed. To improve specificity, the model was limited to the symptoms with the odds ratio >2.0 between the arthralgia and pre-RA group and enriched with information about RA-specific antibodies and survivin in serum. Results: The proposed set of clinical symptoms distinguished the arthralgia patients from RA and from pre-RA. A combination of symptoms in several small joint areas, increasing number of joints with symptoms, and patient’s experience of swelling in small hand joints at the first visit was sufficient to identify pre-RA cases with 92% sensitivity. Presence of survivin in serum showed strong association with clinical joint symptoms. Grouping those symptoms with information about age, gender and serum levels of survivin or autoantibodies in the final algorithm allowed reaching 50% specificity and 55% of positive prediction for transition from arthralgia to RA. Conclusion: Clinical and serological parameters in combination aid recognition of imminent RA among arthralgia patients with appropriate sensitivity.